Hydrophobic CdSe and CdTe quantum dots: shell coating, shape control, and self-assembly. Issue 31 (8th March 2016) - Jiang, Zhixiang; Matras-Postolek, Katarzyna; Yang, Ping
Abstract : Several kinds of hydrophobic quantum dots including CdSe, CdTe, CdSe/Cd x Zn1− x S, and CdTe/CdSe/ZnSe were fabricated via organic synthesis to observe morphology variation during shell coating. Abstract : Several kinds of hydrophobic quantum dots (QDs) including CdSe, CdTe, CdSe/Cd x Zn1− x S, and CdTe/CdSe/ZnSe were fabricated via organic synthesis to observe morphology variation during shell coating. CdSe QDs prepared at a relatively high temperature revealed a hexagonal structure and rod morphology. On being coated with a Cd x Zn1− x S shell, tetrahedron and rod morphologies were observed. It was found that the reaction temperature and injection rate play important roles. The photoluminescence properties of the core/shell QDs depended strongly on their preparation conditions such as temperature and ligands. For CdSe cores created at a relatively low temperature, Cd x Zn1− x S shell coating resulted in the formation of cubic CdSe/Cd x Zn1− x S core/shell QDs. This is ascribed to the role of a CdS interlayer. In contrast, multishell CdTe/CdSe/ZnSe QDs revealed a spherical morphology. Furthermore, the self-assembly of QDs with hexagonal structures occurs while regular assembled structures were not observed for QDs with a cubic morphology according to their transmission electron microscopy images. This is ascribed to a dipole force between QDs. This phenomenon is just related to the morphology and crystal structures rather than their composition.